Comparative Evaluation of Digitization of Diagnostic Dental Cast (Plaster) Models Using Different Scanning Technologies - Aalaa Emara; Neha Sharma; Florian S. Halbeisen; Bilal Msallem; Florian M. Thieringer (MDPI AG, 2020)
Rapidly developing digital dental technologies have substantially simplified the documentation of plaster dental models. The large variety of available scanners with varying degrees of accuracy and cost, however, makes the purchase decision difficult. This study assessed the digitization accuracy of a cone-beam computed tomography (CBCT) and an intraoral scanner (IOS), as compared to a desktop optical scanner (OS). Ten plaster dental models were digitized three times (n = 30) with each scanner. The generated STL files were cross-compared, and the RMS values were calculated. Conclusions were drawn about the accuracy with respect to precision and trueness levels. The precision of the CBCT scanner was similar to the desktop OS reference, which both had a median deviation of 0.04 mm. The IOS had statistically significantly higher deviation compared to the reference OS, with a median deviation of 0.18 mm. The trueness values of the CBCT was also better than that of IOS-median differences of 0.14 and 0.17 mm, respectively. We conclude that the tested CBCT scanner is a highly accurate and user-friendly scanner for model digitization, and therefore a valuable alternative to the OS. The tested IOS was generally of lower accuracy, but it can still be used for plaster dental model digitization.